Mercado imobiliário e estrutura urbana: uma análise da formação de preços de lotes vagos e apartamentos em Belo Horizonte (2009-2020) - Pedro Araújo Patrício (2021)
This dissertation aims to analyse the formation of prices in the market for vacant lots and residential apartments and its relationship with the urban structure in the city of Belo Horizonte, Brazil, from 2009 to 2020, from the perspective of the urban economics. The ideas of William Alonso (1964) formed what is meant by a monocentric model, whose im- plications regarding the organisation of urban space indicate that the commercial center, place of concentration of jobs, is also where the highest prices in the real estate market are verified, while prices decline from that point in the territory. Based on microeconomic grounds, the conclusions anticipate the existence of a spatial equilibrium in the market composed of individuals divided between the search for a better location and greater avai- lability of space. Over the decades, several criticisms have emerged with allegations that it is a model that is not consistent with the urban structure that appeared around the world. However, later contributions gave the model a survivability, in order to consider accessibility as a way of modeling the labor market in a dispersed way in the space. Based on a hedonic price model with different identification strategies for each typology under analysis, the conditions for the formation of prices in these markets for Belo Horizonte in the last decade are investigated. The results show that, on its own, classical theory is not able to understand the urban structure of Belo Horizonte, especially for the residen- tial market. There are parts of the territory with high accessibility via public transport, but low assessed prices, while other parts of the territory have low accessibility and high prices. Vacant lots are more sensitive to accessibility via public transport. However, in order to build a reliable forecast of the values of these two markets, other factors (such as zoning and construction characteristics) also need to be taken into account. Among the limitations of this research is the unavailability of data on individual transport, which could be a mitigating factor for the inconsistency of valued locations with greater distance to the center, as the city center is still accessible by this population resident by private transport. In addition, the research only covers the territory of the municipality of Belo Horizonte, due to the lack of data for the municipalities of the MRBH.